Effect of Nb/B addition on the flow behavior and mechanical properties of low-carbon steel using compact strip production - Ahmed Refaee; Eman El-Shenawy; Aly El Domiaty; Abdalla M. Abdalla; Reham Reda (Scientific Reports)
Abstract This work examines the effects of Nb and Nb-B additives on the high-temperature flow behavior and mechanical properties of low-carbon steel. The base, 0.015% Nb-bearing (15Nb alloy), and 0.015% Nb-30 ppm B-bearing (15Nb30B alloy) low-carbon steels were manufactured at Al Ezz Dekheila Steel Company using the compact strip production line (CSP). The mean flow stress log data from the CSP line was utilized to determine the no-recrystallization temperature. The microstructure and high-temperature flow behavior were studied using thermomechanical controlled processing at different deformation temperatures with a 40% reduction using the Gleeble physical simulator. The phase evolution and precipitation state at various temperatures were studied15Nb30B alloy reveals lower flow stress at high processing temperature in comparison with 15Nb alloy. This is attributed to the early precipitation of BN, which led to restricted Nb-based precipitates. The addition of B to Nb-bearing steel slightly refines the grain size of the as-rolled alloy, which in turn has a beneficial effect on its strength. The research results highlight the industrial benefit of adding boron to Nb-bearing low C-steel in terms of reducing the rolling load and reducing the finishing rolling temperature while maintaining the mechanical properties of the as-rolled strips.